ELECTORAL LAW IN THE NATIONAL CRIMINAL CODE AND THE PRINCIPLES OF CONSTITUTIONAL DEMOCRACY: AN ANALYSIS OF THE LIMITS OF STATE INTERVENTION IN INDONESIA - Muhammad Asmawi (Justisi: Jurnal Ilmu Hukum, 2025)
The development of electoral law in Indonesia has undergone a fundamental transformation following the enactment of Law Number 1 of 2023 on the National Criminal Code (KUHP Nasional), particularly through the codification of electoral offenses into the general criminal law system. This shift signifies an expansion of state intervention into the sphere of electoral democracy, which is inherently connected to citizens’ political rights and the principle of popular sovereignty. This study aims to analyze the rationality of the criminalization of electoral law under the National Criminal Code and to assess the normative limits of state intervention from the perspective of constitutional democracy. The research employs a normative legal method using statutory, conceptual, and constitutional approaches, combined with an analysis of criminalization doctrine, the principle of ultimum remedium, and theories of constitutional democracy. The findings indicate that the criminalization of electoral offenses in the National Criminal Code is not fully grounded in a strict criminalization rationale and carries a significant risk of overcriminalization. Furthermore, the shift of electoral law from a lex specialis regime toward a rigid general criminal law framework has reduced the flexibility of electoral law enforcement and may generate restrictive effects on citizens’ political freedoms. This study argues that state intervention through criminal law in the electoral domain must be proportionally limited and positioned as an ultimum remedium in order to safeguard electoral integrity without undermining the core principles of constitutional democracy.